Picosecond high voltage pulse of framing camera with synchronous trigger and cascade filter - SHUAI Haoming; BAI Yanli; YAO Rongbin; XIE Jun (Shenzhen Daxue xuebao. Ligong ban)
The pulse-dilation framing camera (PDFC) is a composite of pulse-dilation technique and microchannel plate (MCP) framing camera. Its temporal resolution is a nonlinearly fluctuated relation with picoseconds high voltage pulse (PHVP). The PHVP is generated using the model of synchronous triggering and the cascade structure of the LC high-pass filter, which is combined with the cathode voltage and the drift distance that affect temporal resolution, and is applied to the study of time resolution of PDFC. The research results show that the synchronous triggering Marx circuit can generate high voltage pulse with the full width at half maximum (FWHM) better than 1 ns, and when the LC high-pass filter is increased from the first order to the seventh order, FWHM of the PHVP is reduced from 558 ps to 409 ps, the amplitude is decreased from -3.6 kV to -1.4 kV, the slop of the rising edge is nonlinearly fluctuated in the range between 5.03 V/ps and 10.25 V/ps. The temporal resolution of the MCP framing camera is reduced from 206 ps to 149 ps by loading the PHVP on the model of photoelectron multiplication in the channel of the MCP; while the PDFC is loaded by the PHVP, the temporal resolution is nonlinearly fluctuated in the range between 3.8 ps and 39.4 ps by increasing the cathode potential, and drift distance. The temporal resolution of the pulse-dilation framing camera can be optimized by carrying the data statistics and comparisons, when the synchronous trigger Marx circuit is combined with the 3rd order LC high-pass filter circuit.